1990
DOI: 10.1063/1.459638
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform far infrared spectroscopy of the ν′3 vibration of SiC2 in Ar at 10 K

Abstract: A Fourier transform study of the vibrational spectrum of SiC2 produced by vaporizing mixtures of silicon and carbon-12 or carbon-13 at 2900 K and quenching the products in argon at 10 K, has enabled the identification for the first time of the ν″3(b2) vibrational mode, which the results of an earlier matrix study had suggested should lie in the far infrared. The assignment of a frequency observed at 160.4 cm−1 to the ν″3 mode is confirmed by isotopic data and supported by the predictions of ab initio calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…The calculated bond angle of 39.976°for the SiC 2 triangle is in excellent agreement with the experimental angle of 40.4° [40]. The calculated vibrational frequencies 182.2, 760.3, and 1784.9 cm À1 are also in agreement with the experimental data of 160.4, 824.3, and 1741.3 cm À1 [42]. Hence we believe that the BLYP functional and DND basis set used here would reproduce the general features of the SiC nanostructures.…”
Section: Theoretical Methodssupporting
confidence: 81%
“…The calculated bond angle of 39.976°for the SiC 2 triangle is in excellent agreement with the experimental angle of 40.4° [40]. The calculated vibrational frequencies 182.2, 760.3, and 1784.9 cm À1 are also in agreement with the experimental data of 160.4, 824.3, and 1741.3 cm À1 [42]. Hence we believe that the BLYP functional and DND basis set used here would reproduce the general features of the SiC nanostructures.…”
Section: Theoretical Methodssupporting
confidence: 81%
“…Discovery of the 3 0 1 transition 487 cm Ϫ1 above the band origin ended longstanding confusion and sparked further reassignment of the à 1 1 B 2 vibronic structure, while a joint analysis of the 3 1 1 hot band revealed that 3 Љϭ196.37 cm Ϫ1 , or 36 cm Ϫ1 above its argon matrix counterpart. 19 The DF spectra proved to be rich sources of vibrational term energies for the The vibrational analyses of SiC 2 culminated in a 1994 collaboration between Ross and the Sandia group. 33 Stimulated emission pumping ͑SEP͒ of the X 1 A 1 /à 1 B 2 system was implemented to dissect the (0,0, 3 Љ) manifolds for 3 Љ ϭ2, 4, 6, 12, and 14 with full rotational resolution, providing a collection of 11-15 J K a K c levels for each of these largeamplitude bending states.…”
Section: The Proliferation Of Definitive Spectroscopymentioning
confidence: 99%
“…)ϭ837 rather than 852 cm Ϫ1 for the ground state. Finally, in a 1990 investigation 19 the highly anharmonic 3 (b 2 ) vibration was located directly for the first time in the far-infrared region by FTIR spectroscopy, appearing in argon matrices at 160.4, 157.7, and 155.3 cm Ϫ1 for 28 Si 12 C 2 , 28 Si 12 C 13 C, and 28 Si 13 C 2 , respectively. A Jacobitype force field was found to provide the most favorable fit to the isotopomeric frequency data, consistent with a T-shaped molecule exhibiting a nondirectional Si-C 2 bond.…”
Section: The Proliferation Of Definitive Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…4) and Si 2 C (Ref. 6) were observed to be the most abundant species, although weak bands ofSiH 2 , SiH 4 , and SiN 2 provided indirect evidence of the presence of atomic Si.…”
Section: Introductionmentioning
confidence: 96%